Cardiovascular Nursing in Rehabilitative Cardiology: A Review - Izzo, Carmine; Visco, Valeria; Loria, Francesco; Squillante, Antonio; Iannarella, Chiara; Guerriero, Antonio; Cirillo, Alessandra; Barbato, Maria Grazia; Ferrigno, Ornella; Augusto, Annamaria; Rusciano, Maria Rosaria; Virtuoso, Nicola; et al. (Journal of cardiovascular development and disease, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide, necessitating comprehensive management and prevention strategies. Rehabilitative cardiology, also known as cardiac rehabilitation (CR), is a multidisciplinary approach aimed at enhancing recovery, reducing the risk of recurrent cardiac events, and improving patients’ quality of life. This review explores the critical role of cardiovascular nursing in CR, highlighting its contributions to patient education, psychosocial support, and care coordination. Through an analysis of current evidence, we outline the core components of CR, including exercise training, risk factor modification, and behavioral interventions. Cardiovascular nurses play a pivotal role in optimizing patient outcomes by conducting assessments, providing tailored education, and addressing psychological challenges such as depression and anxiety, which often accompany CVDs. Despite the well-documented benefits of CR, participation rates remain low due to barriers such as inadequate referral systems, accessibility challenges, and socioeconomic disparities. Emerging solutions, including telemedicine and home-based CR, offer promising alternatives to improve adherence and accessibility. The review underscores the need for expanded nursing roles, interdisciplinary collaboration, and policy advancements to bridge existing gaps in CR utilization. By integrating innovative care models, cardiovascular nursing can further enhance the effectiveness of rehabilitative cardiology and contribute to improved long-term patient outcomes.